Grundtvig og teatret. Et par bemærkninger i tilknytning til Robert Neiidams Afhandling - Johansen, Steen (Grundtvig-studier, 1950)
Grundtvig and the Theatre. By Steen Johansen. In 1940 the historian of the theatre, Robert Neiiendam, wrote a brief study of Grundtvig and the theatre — by which in the main he meant the Royal Theatre in Copenhagen —, and in 1950 he has published it in expanded form in the book: “ Gennem mange Aar” (During Many Years). Here Mr. Neiiendam has brought together the very few facts that are known about Grundtvig’s relation to the theatre, dramatic art, and actors — a relation which may be described as essentially negative as far as Grundtvig was concerned. (It is not a question here of Grundtvig’s relation to the drama as literature or poetry, though Mr. Neiiendam might have said a little more about this subject.) A distinctive exception to this is to be found in the appearance of the youthful Grundtvig as an amateur actor on two occasions during his student days (1800—03). Until now the only occasion known of was the one when Grundtvig appeared in a play (“ Brevet” i. e. “ The Letter”) written by himself; but it has now become known that he also appeared in a little play by the well*known Norwegian*Danish author P. A. Heiberg. This knowledge, derived from an unpublished diary of Jacob Steenberg, who was one of Grundtvig’s fellow*students, contributes not alone to clarifying several points in Grundtvig’s diary, but also to a better understanding of an (unpublished) play by Grundtvig, dating from his student period.